Comparative Analysis of Performance of Passive and Semi-Active Suspension Systems - Chaurasiya, Suraj Kumar; Khand, Subu; Sarki, Manisha; Labh, Shacheendra Kishor (Journal of Engineering and Sciences, 2025)
The suspension system is a boon to the automotive industry, playing a crucial role in providing ride comfort to passengers. With the advancement of technologies, several studies and innovations in suspension systems have been categorizing them into different types and purposes. This paper analyzes semi-active suspension systems' performance using different control techniques. The suspension system plays a critical role in enhancing the overall ride comfort and stability of vehicles. Employing semiactive suspension systems can adjust the damping characteristics in real-time, leading to improved vehicle dynamics. This investigation uses several control techniques, such as Fuzzy logic control, Proportional Integral Derivative (PID), and Fuzzy PID (FPID) controllers that utilize computer simulations to evaluate the effectiveness of various control techniques for semi-active suspension systems of quarter car models. The performance of the semi-active suspension with control techniques is compared with the passive suspension system in terms of peak overshoot and settling time. Simulation results after comparison show an improvement of 31.37%, 9.85%, and 26.05% using PID, Fuzzy, and FPID-controlled suspension systems.